2013
DOI: 10.5194/amtd-6-3883-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global monitoring of terrestrial chlorophyll fluorescence from moderate spectral resolution near-infrared satellite measurements: methodology, simulations, and application to GOME-2

Abstract: Globally mapped terrestrial chlorophyll fluorescence retrievals are of high interest because they can provide information on the functional status of vegetation including light-use efficiency and global primary productivity that can be used for global carbon cycle modeling and agricultural applications. In addition, fluorescence can contaminate photon path estimates from the O2 A-band that has become an integral part of missions to accurately measure greenhouse gas concentrations. Global mapp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
115
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 51 publications
(64 reference statements)
3
115
0
Order By: Relevance
“…The sun-synchronous orbit with 1:30 p.m. local overpass time will enable mid day SIF measurements similar to the GOSAT but with higher fidelity and much reduced standard error. The very narrow swath of OCO-2 won't allow for truly global retrievals as does GOME-2 (Joiner et al, 2013) but we found that this sampling bias will be small when averaged over regional (e.g. 1 × 1°) scales, thus only hampering local studies either not covered by the OCO-2 swaths or with gradients of interest not properly aligned with the flight track.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The sun-synchronous orbit with 1:30 p.m. local overpass time will enable mid day SIF measurements similar to the GOSAT but with higher fidelity and much reduced standard error. The very narrow swath of OCO-2 won't allow for truly global retrievals as does GOME-2 (Joiner et al, 2013) but we found that this sampling bias will be small when averaged over regional (e.g. 1 × 1°) scales, thus only hampering local studies either not covered by the OCO-2 swaths or with gradients of interest not properly aligned with the flight track.…”
Section: Discussionmentioning
confidence: 97%
“…The first real retrievals were performed using high-resolution spectra of the oxygen A-band region from the Tanso Fourier Transform Spectrometer onboard of the Japanese GOSAT satellite (Hamazaki, Kaneko, Kuze, & Kondo, 2005;Kuze, Suto, Nakajima, & Hamazaki, 2009). Later, Joiner et al (2012) showed that even moderate spectral resolution can be used to infer SIF using either a very broad Fraunhofer line at 866 nm (using SCIAMACHY) or applying a larger spectral range from 715 to 780 nm using GOME-2 (Joiner et al, 2013). In general, there is a trade-off between spectral resolution and spatio-temporal sampling.…”
Section: Introductionmentioning
confidence: 99%
“…We developed a method to calculate a weighted ensemble of GPP from multiple models that best approximate spatial and temporal variations in SIF derived from GOME-2 instrument1424. To improve global estimates of GPP as compared with a straight average of an ensemble of models, we provided a weighted ensemble estimate using three data-driven models (VPM18, MTE25, and MOD1726) and eleven process-oriented models from the TRENDY-v4 project27 (CLM4.5, ISAM, JSBACH, JULES, LPJ, LPJ-GUESS, LPX, OCN, ORCHIDEE, VEGAS, and VISIT, see Materials and Methods).…”
mentioning
confidence: 99%
“…If this is not the case, external information on fluorescence emission is needed to minimize its impact on aerosol retrieval. Note that if the objective of retrieval is to estimate fluorescence emissions, it is much more efficient to use filling-in of Fraunhofer lines outside atmospheric absorption bands, because complicated radiative transfer calculations are not needed (Frankenberg et al, 2011a;Joiner et al, 2011Joiner et al, , 2012bJoiner et al, , 2013Guanter et al, 2012).…”
mentioning
confidence: 99%